A Simulation Approach to Understanding The Effect of Mimicry on Prey’s Flourishing When Predators Decline Due to Environmental Disturbance - Qu, Hongchun; Zou, Kaidi; Zhong, Dandan; Yin, Li; Tang, Xiaoming (Journal of Environmental Accounting and Management, 2026)
Ecological interactions and their consequences to system evolution in the context of environmental disturbance are of special concern in ecological conservation since the environmental conditions have been changing so quickly in the past decades. Understanding how these interactions, particularly the indirect ones such as mimicry, could change prey variabilities in facing of predator loss is an interesting question. In this research, we incorporated Batesian mimicry into a three-species predator prey system to investigate the role of mimicry on regulating prey abundance when the system is suffering predator loss in various patterns. The Netlogo mimicry model was adopted to run the simulation experiments. We found that the timing of predator loss interacting with mimicry can induce significant difference in mimic prey’s abundance if partial predators were removed from the system. However, the variations of frequency of predator loss did not change the mimic prey’s abundance in all conditions. Our findings suggested that indirect interactions can change the final species composition on the long term evolutionary scale if environmental disturbances occur in the particular time window. This is the first report that addresses the question of how indirect interactions such as mimicry affects species bundance when environmental disturbance occurred. We expect that this finding could shed the light on conditions under which species and ecological balance can be better managed when environmental disturbances are inevitable to come.